Valve-in-valve-in homograft: A case of a repeat transcatheter aortic valve replacement in a patient with an aortic homograft - Kimberly Naden Hollander; Mario Montealegre-Gallegos; Feroze Mahmood (Annals of Cardiac Anaesthesia, 2016)
In recent years, the use of transcatheter aortic valve replacement (TAVR) has extended beyond the treatment of native aortic valve stenosis in patients with high surgical risk. TAVR is increasingly being performed for bioprosthetic aortic valve failure, i.e., the valve-in-valve (VIV) procedure. Establishing the success of a VIV procedure can be challenging in these cases. Furthermore, the limited availability of prostheses sizes further complicates the management of these patients. We present an unusual case of a repeat TAVR in a patient who previously had a VIV procedure in an aortic homograft.